Indonesian College Student Defense Mechanism Reflected in Taylor Swift's Anti-Hero - Saputro, Bagas Yudha Gilang; Ananda, Rizmay; Ardianto, Firmansyah Dwi; Jauza, Dhiyanisa Farah; Lowina, Laiya Martha; Saraswati, Rina; Datau, Rizal Octofianto (Faculty of Humanities, Diponegoro University, 2024)
The phenomenon of the youth releasing their feelings to receive a sense of comfort by listening to sad songs cannot be separated from the rising mental health issue, which is in accordance with the increasing amount of sad songs produced by the music industry. Taylor Swift's songs are popular among the youth, especially Indonesian college students who are going through profound and complex emotional journeys relating to identity crises, love, and other unpleasant events, because the lyrics, the melody, and the story present the youth’s experiences. The popularity of Swift's songs among young people is intriguing to study through a psychological lens. Indonesian college students listen to Taylor Swift’s Anti-Hero as an unconscious response to avoid a feeling that they are unable to handle because the song is characterized by its haunting melodies and thought-provoking lyrics. This study aims to examine defense mechanisms in Taylor Swift’s selected song, Anti-Hero, with Indonesian college students. The quantitative-descriptive method is used in this research to assist in describing, showing, or summarizing data constructively, referring to a statistical diagram. This method is used to understand the details of the data by summarizing and finding patterns in certain data samples so that the basic characteristics of the data can be understood and more accurate conclusions can be drawn about the phenomenon being observed. The results obtained are defense mechanisms identified in the response of the targeted respondent, an Indonesian college student, which are repression, denial, displacement, projection, sublimation, and avoidance. As the expression of feeling and emotion, anti-heroism is a form of personal defense based on unconscious acts.